Ore-forming processes of the daqiao epizonal orogenic gold deposit, west qinling orogen, China: Constraints from textures, trace elements, and sulfur isotopes of pyrite and marcasite, and raman spectroscopy of carbonaceous material - Wu, Y.; Li, J.; Evans, Katy; Koenig, A.; Li, Z.; O Brien, H.; Lahaye, Y.; Rempel, Kirsten; Hu, S.; Zhang, Z.; Yu, J. (Society of Economic Geologists Inc, 2018)
The Daqiao gold deposit is hosted in organic-rich Triassic pumpellyite-actinolite facies metamorphosed turbidites in the West Qinling orogen, central China. Gold mineralization is characterized by high-grade hydraulic breccias (B and C ores) that overprint an earlier tectonic breccia (A ore). A complex paragenesis is defined by four sulfide stages: S1 diagenetic preore pyrite (py), S2 hydrothermal early ore disseminated pyrite and marcasite (mc), S3 main ore pyrite and marcasite aggregates, and S4 late ore coarse-grained marcasite with minor pyrite and stibnite. However, multiple generations of pyrite and marcasite may develop within one individual stage. Ore-related hydrothermal alteration is dominated by intensive silicification, sulfidation, sericitization, and generally distal minor carbonatization. Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) trace element analyses show that the stage S1 py1 from the shale interlayers within turbidites contains low gold contents (mean of 0.05 ppm) and other trace elements (Mn, Co, Ni, Cu, Mo, Bi, and Pb), indicating an anoxic to euxinic sedimentary environment. Stage S2 contributed only minimally to the gold endowment with relatively low gold in various sulfides including py2 (mean of 0.09 ppm), py3 (0.84 ppm) to py4 (0.70 ppm), along with mc1 (0.02 ppm) and mc2 (0.14 ppm). Most of the gold was deposited in stage S3, which formed rapidly crystallized, irregular (e.g., framboids, colloform and cyclic zonation) cement-hosted py5a (mean of 27.35 ppm), py5b (9.71 ppm), and mc3 (5.94 ppm) during repeated hydraulic fracturing. Other trace elements (e.g., Ag, As, Sb, Hg, Tl, and W) are also significantly enriched in the main ore-stage pyrite and marcasite. Little or no gold is detected in the S4 py6 and mc4. Sulfur isotopes determined from in situ LA-multicollector (MC)-ICP-MS analyses of hydrothermal pyrite and marcasite from the Daqiao deposit vary significantly from –31.3 to 22.0 (d34S values) but fall mostly between –10 to 10 and provide important information on the source and evolution of sulfur and of the ore-forming fluids. The results show that S2 ore fluids (mean d34Ssulfide = –0.8 to 5.2) were most likely derived from deep-seated Paleozoic carbonaceous sediments during regional metamorphism associated with orogenesis of the West Qinling orogen. Main ore S3 fluids (mean d34Ssulfide = –9.7 to –6.0) are relatively depleted in34S relative to those of S2, presumably due to fluid oxidation associated with hydraulic fracturing caused by the overpressurized fluids. The textural, chemical, and isotopic data indicate two distinct gold-introducing episodes at Daqiao, forming sulfide disseminations during early ore S2 and cement-hosted sulfide aggregates during main ore S3. The S2 mineralization took place in a tectonic breccia beneath low-permeability shale seals that capped the flow of deep-seated metamorphic fluids, facilitating reaction with preexisting carbonaceous material and the host turbidites to form sulfide disseminations and pervasive silicification. Raman spectroscopy analysis suggests that carbonaceous material in the ores is poorly crystallized, with low maturity, giving estimated temperatures of 283° to 355°C that are much higher than those of the ore fluids (100°–240°C). This temperature difference indicates an in situ sedimentary origin modified by the regional pumpellyite-actinolite facies metamorphism for the carbonaceous material in the host rocks, rather than a hydrothermal origin. In S3, continuous flux of hydrothermal fluids caused fluid overpressure and consequent hydraulic fracturing of the competent silicified rocks. Subsequent rapid fluid pressure fluctuations led to phase separation and thus massive oxidation of ore fluids, which triggered fast precipitation of gold and other trace elements within the fine-grained irregular sulfides. Results presented here, in combination with geologic evidences, suggest that the Daqiao gold deposit can be best classified as the shallow-crustal epizonal orogenic type, genetically associated with orogenic deformation and regional metamorphism of the West Qinling orogen.